Society as a learning system: Discovery, invention, and innovation cycles revisited - Marchetti, Cesare (Technological forecasting & social change, 1980)
The very simple heuristic suggestion that society as a whole and its numerous subsets operate like learning systems, basically governed by Volterra-Lotka equations, has been extremely valuable in organizing a most variegated collection of statistical sets of time series, ranging from the structure of energy markets to the efficiency of machinery and the expansion of empires. In this paper an attempt is made to treat invention and entrepreneurship, generally perceived as the most “free” of human activities but actually subject to iron rules. Invention and innovation during the last 250 years appear in precisely structured waves that lend themselves to robust prediction. The present wave will reach its maximum momentum around 1990. Furthermore, the introduction, maximum market penetrations, and prices of new primary energies show a very strong link to these innovation waves. This stresses once more that economic features may be the expression of deeper “physical” phenomena related to the basic working of society and thus become predictable up to a point through a very abstract and noneconomic analysis. This work has been done in the frame of IIASA's Energy Systems Program and can be considered as an outgrowth of and complement to the research on the evolution of energy systems described in IIASA Research Reports 79-12, 79-13, and 77-22. There it was found that a new primary energy coming into the market must be observed for 10 or 20 years if one is to extract the basic features necessary to predict its long-term market behavior. Specifically, it was concluded that the dates at which new primary energies come into play cannot be predicted. In this paper innovations are considered not one by one but as an abstract set, whose behavior is analyzed. In this frame possible birth dates for new energy sources can be identified, thus enhancing the quality of very long-term forecasting in the energy field. Also, prices appear predictable, at least in their gross features.